2019
DOI: 10.1016/j.celrep.2019.01.110
|View full text |Cite
|
Sign up to set email alerts
|

SH3BP4 Regulates Intestinal Stem Cells and Tumorigenesis by Modulating β-Catenin Nuclear Localization

Abstract: Summary Wnt signals at the base of mammalian crypts play a pivotal role in intestinal stem cell (ISC) homeostasis, whereas aberrant Wnt activation causes colon cancer. Precise control of Wnt signal strength is governed by a number of negative inhibitory mechanisms acting at distinct levels of the cascade. Here, we identify the Wnt negative regulatory role of Sh3bp4 in the intestinal crypt. We show that the loss of Sh3bp4 increases ISC and Paneth cell numbers in murine intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Previous studies have identified several crypt-expressing Wnt inhibitors such as AXIN2, RNF43 and SH3BP4 that are involved in CRC development by targeting Wnt signalling pathway at different subcellular levels (Cancer Genome Atlas, 2012;Giannakis et al, 2014, Yan et al, 2017aAntas et al, 2019). In this study, we uncover a new crypt-expressing Wnt regulator NEDD4 that targets two Wnt pathway components LGR4/5 and DVL2 to maintain ISC homeostasis and suppress intestinal tumorigenesis ( Fig 7D).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have identified several crypt-expressing Wnt inhibitors such as AXIN2, RNF43 and SH3BP4 that are involved in CRC development by targeting Wnt signalling pathway at different subcellular levels (Cancer Genome Atlas, 2012;Giannakis et al, 2014, Yan et al, 2017aAntas et al, 2019). In this study, we uncover a new crypt-expressing Wnt regulator NEDD4 that targets two Wnt pathway components LGR4/5 and DVL2 to maintain ISC homeostasis and suppress intestinal tumorigenesis ( Fig 7D).…”
Section: Discussionmentioning
confidence: 62%
“…We then turned to investigating O-GalNAc glycosylation in a multicellular model system. Intestinal organoids are instrumental in understanding some of the key concepts of bowel cancer formation as well as normal gut development and homeostasis ( 48 52 ). Production of O-GalNAc glycans in such systems is often probed by either backbone-directed antibodies or lectins ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Histology revealed moderate osteoarthritis with articular cartilage fibrillations and vertical clefts over <25% of the articular surface extending to the calcified cartilage beneath (OARSI grade 3) (Figure 4, Supplementary Figure 4 and Supplementary Table 3). Sh3bp4 is a poorly characterized SH3 domain binding protein involved in transferrin receptor (TfR) internalization 43 , fibroblast growth factor receptor (FGFR) trafficking 44 , mammalian target of rapamycin (mTOR) signalling 45 and inhibition of the Wnt pathway 46 . SH3BP4 has not been associated with osteoarthritis in GWAS.…”
Section: Early Onset Osteoarthritis In Bhlhe40 -/And Sh3pb4 -/Mutant mentioning
confidence: 99%